2019
DOI: 10.1097/bor.0000000000000633
|View full text |Cite
|
Sign up to set email alerts
|

Complement, infection, and autoimmunity

Abstract: Purpose of review Complement system dysfunction in terms of upregulation, downregulation, or dysregulation can create an imbalance of both host defense and inflammatory response leading to autoimmunity. In this review, we aimed at describing the role of complement system in host defense to inflection and in autoimmunity starting from the evidence from primary and secondary complement system deficiencies. Recent findings Complement system has a determinant role in defense against infections: deficiencies of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 98 publications
3
76
0
Order By: Relevance
“…However, this decrease was not as prominent as the reduced IgG2 concentrations in BP, but this finding also warrants follow-up and validation in prospective studies. Of note, patients with primary complement deficiencies are also prone to developing autoimmune diseases (21,22). In BP patients, plasma concentrations of C3a, C4a, and C5a are identical to those of age-and sex-matched controls (23).…”
Section: Discussionmentioning
confidence: 96%
“…However, this decrease was not as prominent as the reduced IgG2 concentrations in BP, but this finding also warrants follow-up and validation in prospective studies. Of note, patients with primary complement deficiencies are also prone to developing autoimmune diseases (21,22). In BP patients, plasma concentrations of C3a, C4a, and C5a are identical to those of age-and sex-matched controls (23).…”
Section: Discussionmentioning
confidence: 96%
“…Though complement is a stakeholder of a healthy immune system, uncontrolled activation of complement leads to inflammation (Conigliaro et al 2019 ). It was revealed that the viruses interact with complement components and its receptors to escape from the host-defense mechanisms (Lindahl et al 2000 ).…”
Section: Complement Cascade and Sars-cov-2mentioning
confidence: 99%
“…Duly, the complement system is a wing of an innate immune response having multifaceted biological effects against a wide range of bacterial, fungal, and viral infections. The complement cascade consists of soluble factors and cell surface receptors that can sensitize and counteract against both invading- (Stoermer and Morrison 2011 ) and self-antigens (Conigliaro et al 2019 ). The complement system bridges the innate and adaptive immune response through humoral immunity, and by modulating T- and B-cell functions (Carroll 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These functions have been widely researched and are not only critical for mediating protection against bacterial pathogens, 1 but can also contribute to tissue damage when dysregulated, for instance in animal models of systemic lupus erythematosus, 2 myasthenia gravis 3 and autoimmune uveoretinitis 4 . Therefore, when this system fails, as can occur in people with rare hereditary deficiencies or due to chronic inflammation, the consequences can be extremely serious, leading to persistent infections or autoimmunity 5 …”
mentioning
confidence: 99%